2023
DOI: 10.1037/abn0000855
|View full text |Cite
|
Sign up to set email alerts
|

Capturing mood dynamics through adolescent smartphone social communication.

Lilian Y. Li,
Esha Trivedi,
Fiona Helgren
et al.

Abstract: Most adolescents with depression remain undiagnosed and untreated—missed opportunities that are costly from both personal and public health perspectives. A promising approach to detecting adolescent depression in real-time and at a large scale is through their social communication on the smartphone (e.g., text messages, social media posts). Past research has shown that language from online social communication reliably indicates interindividual differences in depression. To move toward detecting the emergence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 70 publications
(119 reference statements)
0
9
0
Order By: Relevance
“…Exploratory analyses of data-driven LDA topics revealed that a language topic reflecting feelings was associated with increased risk for concurrent MDD, extending cross-sectional research linking feelings-related words to depression (Li et al, 2023;Liu et al, 2022;Stamatis et al, 2022;Tølbøll, 2019). Additionally, less judgment -a topic primarily reflecting positive and negative appraisals (e.g., funny, stupid) -was associated with greater MDD risk.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…Exploratory analyses of data-driven LDA topics revealed that a language topic reflecting feelings was associated with increased risk for concurrent MDD, extending cross-sectional research linking feelings-related words to depression (Li et al, 2023;Liu et al, 2022;Stamatis et al, 2022;Tølbøll, 2019). Additionally, less judgment -a topic primarily reflecting positive and negative appraisals (e.g., funny, stupid) -was associated with greater MDD risk.…”
Section: Discussionmentioning
confidence: 54%
“…We used each app's classification and description in the Apple App Store and/or Google Play Store to determine whether it was primarily for social communication (Li et al, 2023;McNeilly et al, 2023). The most used social communication apps were messaging (e.g., Messaging, Discord, Kakao) and social media apps (e.g., Snapchat, Instagram; see Figure S1 for a list of all included apps).…”
Section: Smartphone Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Adolescents (ages 13-18 years old; N = 148) were recruited from the greater New York City and Chicago communities through social media advertisements, as part of a multisite longitudinal study of social processes in adolescent depression (Li et al, 2023). No SGM-targeted recruitment strategies were employed.…”
Section: Methodsmentioning
confidence: 99%